SKLERODERMALI BİR OLGUDA DUYSAL TRİGEMİNAL NÖROPATİ - GÜNDÜZ, Ayşegül; AKALIN, Mehmet Ali; KIZILTAN, Meral E. (Cerrahpaşa Medical Journal, 2014)
Background and Design.- Trigeminal neuropathy is characterized by numbness of face, weakness or trismus of masticatory muscles. Trigeminal neuropathy is reported in 4% of scleroderma cases. Here we present trigeminal neuropathy in a case of scleroderma with trigeminal reflex investigations. Clinical findings and electromyographic investigations of a 65 year old patient with known scleroderma for two years was diagnosed as trigeminal neuropathy. Gabapentin 900mg/day provided symptomatic relief at fourth month control. With cranial MRI, intracranial lesion that may cause trigeminal symptomatology was excluded. Microinfarction or inflammation due to scleroderma was the possible causes of trigeminal neuropathy in this patient.